Current Status, Challenges, Policies, and Bioethics of Biobanks - Byunghak Kang; Jaesun Park; Sangyun Cho; Meehee Lee; Namhee Kim; Haesook Min; Sooyoun Lee; Ok Park; Bokghee Han (Genomics & Informatics)
Many biobanks were established as biorepositories for biomedical research, and a number of biobanks were founded in the 1990s. The main aim of the biobank is to store and to maintain biomaterials for studying chronic disease, identifying risk factors of specific diseases, and applying personalized drug therapies. This report provides a review of biobanks, including Korean biobanks and an analysis of sample volumes, regulations, policies, and ethical issues of the biobank. Until now, the top 6 countries according to the number of large-scale biobanks are the United Kingdom, United States, Sweden, France, the Netherlands, and Italy, and there is one major National Biobank of Korea (NBK) and 17 regional biobanks in Korea. Many countries have regulations and guidelines for the biobanks, and the importance of good management of biobanks is increasing. Meanwhile, according to a first survey of 456 biobank managers in the United States, biobankers are concerned with the underuse of the samples in their repositories, which need to be advertised for researchers. Korea Biobank Network (KBN) project phase II (2013-2015) was also planned for the promotion to use biospecimens in the KBN. The KBN is continuously introducing for researchers to use biospecimens in the biobank. An accreditation process can also be introduced for biobanks to harmonize collections and encourage use of biospecimens in the biobanks. KBN is preparing an on-line application system for the distribution of biospecimens and a biobank accreditation program and is trying to harmonize the biobanks.